Assessment of the Risk of Amazon Dieback - Vergara, Walter; Scholz, Sebastian M. (World Bank, 2012)
The Amazon basin is a key component of the global carbon cycle. The old-growth rainforests in the basin represent storage of ~ 120 petagrams of carbon (Pg C) in their biomass. Annually, these tropical forests process approximately 18 Pg C through respiration and photosynthesis. This is more than twice the rate of global anthropogenic fossil fuel emissions. The basin is also the largest global repository of biodiversity and produces about 20 percent of the world's flow of fresh water into the oceans. Despite the large carbon dioxide (CO2) efflux from recent deforestation, the Amazon rainforest ecosystem is still considered to be a net carbon sinks of 0.8-1.1 Pg C per year because growth on average exceeds mortality (Phillips et al. 2008). However, current climate trends and human-induced deforestation may be transforming forest structure and behavior (Phillips et al. 2009). Increasing temperatures may accelerate respiration rates and thus carbon emissions from soils (Malhi and Grace 2000). High probabilities for modification in rainfall patterns (Malhi et al. 2008) and prolonged drought stress may lead to reductions in biomass density. Resulting changes in evapo-transpiration and therefore convective precipitation could further accelerate drought conditions and destabilize the tropical ecosystem as a whole, causing a reduction in its biomass carrying capacity or dieback. In turn, changes in the structure of the Amazon and its associated water cycle will have implications for the many endemic species it contains and result in changes at a continental scale. Clearly, with much at stake, if climate-induced damage alters the state of the Amazon ecosystem, there is a need to better understand its risk, process, and dynamics. The objective of this study is to assist in understanding the risk, process, and dynamics of potential Amazon dieback and its implications.